An alternative benchmarking tool for operational energy efficiency of ships and its policy implications. (10th December 2019) - Zhang, Shuang; Li, Ying; Yuan, Haichao; Sun, Deping
Abstract: Greenhouse gases and other air pollutants emitted from ships account for an unneglectable proportion of the global total. Given the generally high correlation between fuel consumption and emissions, improving the energy efficiency of ships is an important pathway towards cleaner shipping while ensuring sustainable development. In developing a global mechanism for the energy efficiency of ships, an appropriate indicator is a prerequisite for performance benchmarking. Yet due to commercial sensitivity or distorted metric results, the existing indicators are widely questioned. To address these shortcomings, an alternative metric, called Energy Efficiency Performance Indicator (EEPI), is proposed by this paper through semi-empirical analyses. Through introducing a novel proxy of "transport work" informed by the estimation results of an unobserved effects model and quantile regressions, EEPI can yield rational metric results without relying on commercially-sensitive data. Given its simplicity, practicability, unbiasedness and adaptability to the existing policy framework, EEPI can be potentially used as a benchmarking tool, alone or in conjunction with a rating mechanism, to create incentives for better energy efficiency performance and cleaner operation. Though derived from oil tankers, EEPI is theoretically applicable to other cargo ships that share similar operational patterns, such as bulk carriers and liquid chemical tankers. It is also potentially applicable to other ship types with certain revisions. Given the challenges of its application in practice, however, EEPI proposed by this paper can be regarded as a prototype for further improvement. Highlights: An alternative operational energy efficiency indicator (EEPI) is proposed. Unobserved effects are taken into account taking merits of panel data set. EEPI overcomes vital shortcomings of other candidate indicators. Performance of EEPI in practice is demonstrated based on statistical data. EEPI can serve as a benchmarking tool for stimulating cleaner marine operation.